2016
DOI: 10.1177/1359105315581515
|View full text |Cite
|
Sign up to set email alerts
|

Understanding how adolescents and young adults with cancer talk about needs in online and face-to-face support groups

Abstract: We compared adolescent and young adult cancer patient and survivor language between mediated and face-to-face support communities in order to understand how the use of certain words frame conversations about family, friends, health, work, achievement, and leisure. We analyzed transcripts from an online discussion board ( N = 360) and face-to-face support group ( N = 569) for adolescent and young adults using Linguistic Inquiry and Word Count, a word-based computerized text analysis software that counts the fre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
38
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 35 publications
(39 citation statements)
references
References 32 publications
1
38
0
Order By: Relevance
“…There is a tendency for young adult men to receive support from individuals who are struggling with similar concerns by engaging in online activities. In fact, qualitative findings from young adult men with cancer demonstrate that they are more open to talking about cancer-related concerns on an online platform than in face-to-face conversations (Love et al, 2014; Thompson et al, 2015). Comparisons between young adult online cancer support groups and face-to-face support groups showed significant differences in mean word frequencies for words related to anger, sadness, causation, and inhibition (Thompson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…There is a tendency for young adult men to receive support from individuals who are struggling with similar concerns by engaging in online activities. In fact, qualitative findings from young adult men with cancer demonstrate that they are more open to talking about cancer-related concerns on an online platform than in face-to-face conversations (Love et al, 2014; Thompson et al, 2015). Comparisons between young adult online cancer support groups and face-to-face support groups showed significant differences in mean word frequencies for words related to anger, sadness, causation, and inhibition (Thompson et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Matthews and colleagues [65] found several topics of disclosure, such as sex, psychological problems, and family relationships, to be deemed as highly personal by YAs, and online support communities may be less risky environments to discuss these topics [66]. Additionally, Thompson and colleagues [66] found that family-related word usage in online cancer survivorship communities was positively correlated with future tense verbs, something that was also associated with nonresponse in the present study. It may be that users are using future tense to speak about their family issues and may not be getting replies.…”
Section: Topic Selectionmentioning
confidence: 56%
“…These types of platforms allow young adults to interact with their peers and support network as well as with other cancer patients about their diagnosis and its impact on their lives without needing to be in the same physical space . Indeed, studies have started to analyze narrative content and structure of online young adult cancer social support groups . One study comparing across an online social support group and a face‐to‐face communication group found that content expressed online contains greater expression of anger and sadness and more references to friends and sexual topics compared with face‐to‐face communication whereby more positive emotion was expressed .…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, studies have started to analyze narrative content and structure of online young adult cancer social support groups . One study comparing across an online social support group and a face‐to‐face communication group found that content expressed online contains greater expression of anger and sadness and more references to friends and sexual topics compared with face‐to‐face communication whereby more positive emotion was expressed . However, research examining the effectiveness of eliciting social support through technology‐related communication is limited, and results are mixed; majority of this work has focused on the impact of text messaging suggesting that texting specifically is associated with a greater sense of connection and satisfaction in close relationships …”
Section: Introductionmentioning
confidence: 99%